Characteristics of the placement and permanence in temporary central venous catheters for hemodialysis in a public hospital 2015-2019 - Venegas Justiniano, Joanna Yanissa (2022)
Objective: To describe the characteristics and permanence of temporary central venous catheters (CVCT) for hemodialysis in the Nephrology Service of a public Hospital in the period 2015-2019. Methods: Retrospective cohort longitudinal analytical study. 2156 records of CVCT placement procedures for hemodialysis in patients with stage 5 chronic kidney disease (CKD-5) were included, the final condition of the catheters was recorded during the follow-up period. Patients lost to follow-up were excluded. Results: Twenty-one hundred and fifty-six procedures were evaluated in 1,650 patients. Locations of catheters were Jugular, 1019 (51,9%); Subclavian, 198 (9,2%); and Femoral 129 (5,9%). Main causes of withdrawal were catheter dysfunction in 730 cases (33,9%) and infection in 410 (19,1%). During the five-year course, changes were observed, such as: variation in starting hemodialysis with AVF from 9.6% to 17,1% (p = 0,042), placement of tunneled CVCs during the first year of starting hemodialysis, from 8% to 23,0% (p 60 years), and diabetic etiology. During the study period, the variations in the proportion of patients who start chronic hemodialysis therapy with AVF are very low.